Recombinant human granulocyte-macrophage colony-stimulating factor therapy and endogenous plasma GM-CSF, IL-3, IL-4 concentrations in pediatric patients with solid tumors - Çetingül, Nazan; Kütükçüler, Necil; Kantar, Mehmet; Kavaklı, Kaan; Nişli, Güngör; Çağlayan, Suat; Öztop, Senay (The Turkish Journal of Pediatrics, 1997)
Ten pediatric patients with solid tumors and chemotherapy-induced neutropenia were given recombinant human granulocyte-macrophage colony-stimulating factor (rHuGM CSF). The duration of the neutropenic phase was then compared with the results obtained from eight patients also with solid tumors, but not treated with rHuGM-CSF. It was found that rHuGM-CSF treatment significantly decreased the duration of the neutropenic phase. Endogenous plasma GM-CSF, IL-3, and IL-4 levels were also measured in the study group and in healthy children. No significant correlation has been found between plasma GM-CSF concentrations and absolute neutrophil counts. However, IL-3 levels of the neutropenic patients positively correlated with platelet counts. Furthermore, IL-4 concentrations were positively correlated with the GM-CSF level in the same individual. Plasma GM-CSF, IL-3, and IL-4 levels in the neutropenic solid tumor group were found to be significantly higher than those in healthy children. Plasma IL-4 levels were significantly elevated in patients with osteosarcoma as compared to patients with other solid tumors. Although rHuGM-CSF has a half-life of only two to three hours, one day after rHuGM-CSF therapy, plasma GM-CSF levels were found to be higher than initial values. In contrast, plasma IL-4 values decreased significantly after administration of rHuGM-CSF. The probable mechanisms for the changes in cytokine levels are discussed.